The Antimicrobial Activities of Nanoparticles against Helicobacter Pylori: A Systematic Review - Shakib, Pegah; Saki, Reza; Goudarzi, Gholamreza; Zolfaghari, Mohammad R. (Current Bioactive Compounds, 2024)
Background: Helicobacter Pylori is widely present in human populations, making it one of the most common bacteria found in humans. Due to the drug's side effects, extensive research is being done to find new effective nanoparticles against Helicobacter Pylori in the world. Therefore, this systematic review aims to investigate nanoparticles' antimicrobial activities against Helicobacter Pylori. Methods: All articles published from 2000 to 2023 from Scopus, PubMed, Science Direct, Cochrane, and Ovid databases with keywords Helicobacter Pylori, H.pylori, nanoparticles, solid lipid NPS, and lipid nanocarrier were extracted and transferred to EndNote X9 software by two researchers. Results: During the first stage, 280 articles were chosen. Following the application of the eligibility criteria for inclusion/exclusion, 37 studies were ultimately selected, considering the removal of duplicates, irrelevant articles, and those containing complete text. In the present systematic review study, most nanoparticles used against Helicobacter Pylori were polymericbased nanoparticles. Conclusion: The results indicate the high potential of various nanoparticles against Helicobacter Pylori. Therefore, the results show that these nanoparticles have the potential to prepare anti- Helicobacter Pylori nanoparticles. In addition, these nanoparticles have fewer side effects than chemical drugs.
Keywords: nanoparticles (NPs)